Walking ability and quality of life in subjects with transfemoral amputation: a comparison of osseointegration with socket prostheses - Van de Meent, Hendrik; Hopman, Maria T; Frölke, Jan Paul (Archives of physical medicine and rehabilitation, 2013)
To investigate walking ability and quality of life of osseointegrated leg prostheses compared with socket prostheses. Prospective case-control study. University medical center. Subjects (N=22) with transfemoral amputation (1 bilateral) referred to our center because of socket-related skin and residual limb problems resulting in limited prosthesis use. Their mean age was 46.5 years (range, 23-67y) and mean time since amputation was 16.4 years (range, 2-45y). Causes of amputation were trauma (n=20) and tumor (n=2). Implantation of an osseointegration prosthesis (OIP). Global score of the Questionnaire for Persons With a Transfemoral Amputation (Q-TFA), prosthesis use, 6-minute walk test (6MWT), Timed Up & Go (TUG) test, and oxygen consumption during treadmill walking. With the socket prosthesis, the mean ± SD Q-TFA global score, prosthesis use, 6MWT, TUG, and oxygen consumption were 39±4.7 points, 56±7.9h/wk, 321±28m, 15.1±2.1 seconds, and 1330±310mL/min, respectively, and significantly improved with OIP to 63±5.3 points, 101±2.4h/wk, 423±21m, 8.1±0.7 seconds, and 1093±361mL/min, respectively. Osseointegration is a suitable intervention for persons whose prosthesis use is reduced because of socket-related problems. Subjects with OIP significantly increased their walking ability and prosthesis-related quality of life.